Theoretical aspects of the effectiveness of economic damage assessment in the field of environmental auditing: problems and solutions - N. G. Gadzhiev; S. A. Konovalenko; M. N. Trofimov; Kh. G. Akhmedova; M. Z. Gadzhidadaev; U. A. Gadzhieva (Юг России: экология, развитие, 2021)
Aim. The aim of the research has been: to study the theoretical basis of the application of assessment of economic damage from environmental pollution in the field of environmental auditing and accounting, to identify problems in existing methods and approaches and to propose specific ways to solve them taking into account current legislation and international experience.Material and Methods. The research carried out by the authors was based on the provisions of current legal regulations in the fields of environmental safety and environmental protection, damage assessment in the environmental sphere together with data from scientific articles by both domestic and foreign experts in the field of environmental auditing. The study was conducted using theoretical methods of research including analysis, deduction and prediction.Results. The authors propose moving away from traditional cost (taxation) methods to the consolidation in regulatory practice of a single approach to the assessment of economic damage taking into account actuarial valuation methodology, application of sanctions instruments to those unscrupulously infringing environmental regulations and the possibility of discounting the costs of restoring the environment and damage done to public health.Conclusion. Adoption of common approaches and principles in the assessment of economic damage will help eliminate negative manipulations when imposing economic sanctions on those unscrupulously engaged in activities impacting on the environment and will provide an opportunity to improve the environmental situation and public health in the long term.